Student’s criteria for higher educational institution / Nur Mas Merah Suraya Jumadil - Jumadil, Nur Mas Merah Suraya (Faculty of Business and Management, 2010)
The 1990’s represented an era of rapid development for the Malaysian private higher educational institutions and was characterized by the growth in the number of institutions, variety of courses offered and course structures. According to Marzita (2005), there were 535 private colleges and 26 private universities and university colleges registered with the Ministry of education in 2005. In 2010 the amount is increasing rapidly and it has been update by the Ministry of education that student enrolment also increases. This paper attempts to determine the criteria that influence a student when they choosing institutional of higher learning to continue study. Using a sample of 60 respondents, the researcher intends to determine the criteria based on 15 independent variables; size of the institution, location, MQA accreditation, type of institution, this study used frequency, reliability, cross tabulation and mean. From the finding, it can be concluding that most of the respondents looking at the certain area and criteria when they want to continue study like cost, courses offered and campus facilities. Private institution of higher learning has critical circumstances when they want to gain student especially when the new intake is taken place. This research can assist them in some areas that need improvement and development. This is important to make sure that customer who is student is always satisfied and always exceed their expectation moreover they can improve on the critical area or the area that they miss out. Lastly, changes are needed from time to time to meets customers’ or student expectation because different student have different expectation towards the institution of higher learning.